Tanggung Jawab Pidana Korporasi Rumah Sakit - Buamona, Hasrul (Faculty of Law, Universitas Ahmad Dahlan, 2016)
Hospital is an institution that provides comprehensive health services on preventive, promotive, curative and rehabilitative to the public at largeas regulated in Article 1 (3) of Law Number 44 Year 2009 About the Hospital, which says